2023
DOI: 10.3390/su15097160
|View full text |Cite
|
Sign up to set email alerts
|

Use of Phosphoric Acid and Rice Hulk Ash as Lateritic Soil Stabilizers for Paving Applications

Abstract: Phosphoric acid (H3PO4) is a product that can be used as a stabilizing additive for tropical soils in an exploratory manner by the construction industry. For the drying process of this grain, its husks are used as fuel for ovens, generating rice husk ash (RHA), which is considered an environmental liability if not reused. In this sense, this paper aimed to evaluate the resilient behavior and the simple compressive strength, at different curing ages, of the use of rice husk ash and phosphoric acid in a simple a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…After conducting a comparative analysis of the findings obtained in the current study and previous studies, it was seen that there exist notable resemblances between the outcomes of the current investigation and previous scholarly inquiries RHA-UCS pertaining to RAH. Previous studies have utilized rice husk ash as a sole component, with a ratio ranging from 10%-15% depending on the soil type [17,[29][30][31][32]. However, another study has found that a 10% proportion of rice husk ash as a partial replacement for cement in aerated concrete yields beneficial effects on the strength and durability properties of the concrete.…”
Section: Figure 10 Mixture Effect On the Ucsmentioning
confidence: 99%
“…After conducting a comparative analysis of the findings obtained in the current study and previous studies, it was seen that there exist notable resemblances between the outcomes of the current investigation and previous scholarly inquiries RHA-UCS pertaining to RAH. Previous studies have utilized rice husk ash as a sole component, with a ratio ranging from 10%-15% depending on the soil type [17,[29][30][31][32]. However, another study has found that a 10% proportion of rice husk ash as a partial replacement for cement in aerated concrete yields beneficial effects on the strength and durability properties of the concrete.…”
Section: Figure 10 Mixture Effect On the Ucsmentioning
confidence: 99%
“…The enhanced strength and stiffness of the soil, even after short-term curing, were attributed to the hydration reactions of calcium-rich PFA, leading to the formation of stable cementitious compounds. Silva et al (2023) investigated rice husk ash (RHA) as a stabilizing additive for lateritic soil [14]. Their research emphasized the combined effect of RHA and phosphoric acid on the soil's resilient behavior and compressive strength.…”
Section: Introductionmentioning
confidence: 99%
“…The selection of additive type mainly relies on soil characteristics, environmental climate, the aim of the improvement, environmental benefits, and cost-effectiveness [7]. Calcium-based conventional binders such as cement, lime, and fly ash are widely used in soil stabilization [8][9][10][11][12]. However, as the sulfate concentration in the environment increases, these materials allow the formation of harmful minerals such as ettringite and thausamatite, thus negatively affecting the soil strength.…”
Section: Introductionmentioning
confidence: 99%